2001
DOI: 10.1046/j.1439-0531.2001.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Fertilizing Capacity of Deep Frozen Boar Semen Packaged in 0.5 and 5 ml Straws

Abstract: The aim of this study was to evaluate the straw size effect used for freezing on the in vitro fertilizing capacity. Twenty-one ejaculates from seven fertile boars were frozen under controlled conditions in 0.5 and 5 ml straws. Thawed semen was compared to fresh semen. For fresh and thawed semen in 0.5 and 5 ml straws, the results were: 92.18, 77.38 and 79.04% sperm penetration; 80.68, 66.89 and 69.33% monospermy; 11.51, 10.49 and 9.74% polyspermy; 86.19, 47.14 and 47.02% motility and 75.52, 48.19 and 46.81% no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Cryopreservation has been reported to affect sperm motility and viability and increase ROS-induced oxidative stress, DNA fragmentation, and apoptosis [13,43,44]. Cryopreservation has also been linked to calcium homoeostasis, acrosome integrity, structural and functional alterations in sperm plasma membranes, which could result in leakage of essential intracellular enzymes such as antioxidants, acrosin, aspartate aminotransferase (AspAT), or energy substrates (i.e., adenosine triphosphate (ATP)), and ultimately lead to cell death [2,45].…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation has been reported to affect sperm motility and viability and increase ROS-induced oxidative stress, DNA fragmentation, and apoptosis [13,43,44]. Cryopreservation has also been linked to calcium homoeostasis, acrosome integrity, structural and functional alterations in sperm plasma membranes, which could result in leakage of essential intracellular enzymes such as antioxidants, acrosin, aspartate aminotransferase (AspAT), or energy substrates (i.e., adenosine triphosphate (ATP)), and ultimately lead to cell death [2,45].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the IVF is shown as a precise technique to assess freezing procedures of boar semen. In this way, a limited number of factors related with the freezing process have been evaluated by the use of an IVF system (holding time and type of package (Eriksson et al 2000) or volume of straw (Cordova et al 2001, 2002). As conclusion, we can determine that a fast thawing speed had a more positive effect on the fertilizing capacity in vitro of the frozen boar semen.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Córdova et al. () found no differences between 0.5‐ and 5‐ml straws in terms of post‐thaw sperm quality, total penetration, monospermy and polyspermy rates, and Eriksson et al. () reported post‐thaw sperm motility was higher when 5‐ml FlatPacks were used.…”
Section: Cooling Rates and Sperm Packagingmentioning
confidence: 99%